Is There a Rise in the Importance of Socioemotional Skills in the Labor Market? Evidence From a Trend Study Among College Graduates - Allen, Jim; Belfi, Barbara; Borghans, Lex (Frontiers in Psychology, 2020)
In this study, we examine whether socioemotional skills have become more important in the labour market within the past 14 years. To this end, we analyze data from a unique dataset on recent graduates from Dutch professional colleges (N = 67,000). Two different indicators of skill change are investigated, namely changes in the skill level required in the labor market and changes in the wage returns to these skills. The results indicate that socioemotional skills related to knowledge and innovation such as logical reasoning and information gathering, as well as skills related to working to plan and collaboration, have undergone a significant increase in terms of labor market requirements. We also observe an increase in the required level of the work-related skills digital literacy and occupation-specific knowledge. However, significant increases in wage returns are only observed for socioemotional skills related to knowledge and innovation, as well as for the work-related skill digital literacy. The labor market importance of socioemotional skills appears to be only modestly affected by business cycle effects.